2016
DOI: 10.1353/hpu.2016.0158
|View full text |Cite
|
Sign up to set email alerts
|

Assessing health literacy levels of Spanish-speaking Hispanic patients in Spanish at federally qualified health centers (FQHCs) in the Midwest

Abstract: Low levels of health literacy reported in this study are consistent with previous assessments. We observed statistically significant differences in LHLL based on gender, education level, and country of origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Based on the results from the National Assessment of Adult Literacy, Hispanics have the lowest average health literacy level compared to all racial/ethnic group (Kutner et al, 2006). Results from a study conducted in rural and urban Hispanic populations in the Midwest were also consistent with the national statistics in terms of low health literacy levels (De Alba et al, 2016).…”
supporting
confidence: 74%
“…Based on the results from the National Assessment of Adult Literacy, Hispanics have the lowest average health literacy level compared to all racial/ethnic group (Kutner et al, 2006). Results from a study conducted in rural and urban Hispanic populations in the Midwest were also consistent with the national statistics in terms of low health literacy levels (De Alba et al, 2016).…”
supporting
confidence: 74%
“…In the United States, Andrulis and Brach (2007) calculated that approximately 40% of adults have limited health literacy, and that over one-half of them are nonwhite and/or Hispanic. Brice et al (2008) found low health literacy levels in Spanish-speaking patients in an emergency department, and Alba, Britigan, Lyden, and Johansson (2016) demonstrated similar results in Spanish-speaking patients in federally qualified health centers across the Midwestern U.S. Functional health literacy has been described as “the degree to which individuals have the capacity to obtain, process, and understand basic health information and services needed to make appropriate health decisions” (Kindig, Panzer, & Nielsen-Bohlman, 2004). This definition is undergoing continual revision as research in the field advances and as researchers move away from a “deficit model” toward a realization that health literacy is a social construct that is variable and interdependent on social, economic, demographic, and other unknown factors (Pleasant, 2014).…”
mentioning
confidence: 99%
“…Further, despite research that shows minority populations have inequitable educational attainment, particularly in older populations [ 25 ], past research has found that minority populations do not reap the same health benefit from educational attainment as their white counterparts; given the same education, disadvantaged and marginalized groups are at an increased risk for unhealthy behaviors and health outcomes when compared to whites [ 26 ]. Previous research has found that lower educational attainment was associated with lower health literacy levels, especially among minority populations [ 27 ], further demonstrating the importance of identifying those with low levels of education and it connection with one’s health literacy and health outcomes. These health inequities may be due to underlying social determinants that are exacerbated among minority populations, such as racial discrimination and lack of access to other social resources.…”
Section: Discussionmentioning
confidence: 99%